(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Five fungicides viz., CM 75, Dithane M 45, Knowin 50 WP, Nativo 75 WG and Rovral 50 WP were evaluated against Colletotrichum lindemuthianum, Drechslera sacchari and Fusarium semitectum following poisoned food technique. Out of five fungicides complete inhibition of radial growth of C. lindemuthianum was observed in Nativo 75 WG at 100 ppm. On the other hand, the complete inhibition of the growth of D. sacchari was observed with Rovral 50 WP at 400 ppm, whereas Nativo 50 WP showed complete growth inhibition at 500 ppm. CM 75 WP, Knowin 50 WP and Nativo 75 WG showed complete growth inhibition of F. semitectum at 100 ppm. Five different plant leaf extracts viz., Azadirachta indica A. Juss., Heliotropium indicum L., Lippia alba L., Michelia champaca L. and Thuja occidentalis L. were tested against the test pathogens. Of the five plant leaf extracts, Lippia alba showed the highest growth inhibition in C. lindemuthianum, D. sacchari and F. semitectum at 20% concentration. J. Asiat. Soc. Bangladesh, Sci. 46(1): 81-89, June 2020